Analyzing Influence on Inflation, Export, Exchange Rate, and Labor Cost to FDI in Indonesia for Period 2000-2012 - Hartini, Nursanthy Indah; Noveria, Ana (Journal of Business and Management, 2014)
FDI is defined as investment inflow to a country other than investor’s country to obtain long term interest or management control over companies operating in a host country. FDI can occur in the types of purchasing existing asset in a foreign country, to joint venture with a local company. This research will explain about the influences of inflation, export, exchange rate, and labor cost to FDI inflows in Indonesia. The data of FDI inflows are gathered from Asian Development Bank Institute in a quarterly basis for the period 2000 to 2012. To analyze the data, multiple linear regression is used to determine which variables give significant impact to FDI, and Granger Causality to observe if there is any causality relationship either in one way or two ways. The independent variables are inflation, export, exchange rate, and labor cost. The independent variables in this research were chosen based on the FDI theories. The data for the independent variables were gathered from Bank Indonesia and Badan Pusat Statistik. Before proceeding with the regression, the assumption test is done to ensure that the regression model is valid to be analyzed. After the assumption test is conducted and the variables are proven to be valid for regression, the hypothesis testing is conducted. It is found that only two variables give significant influence to FDI, which are export and labor cost. Both export and labor cost affects FDI in a positive relationship. Thus, it proves that open export economies tend to attract FDI inflows. It also proves that although labor cost influence FDI, lower labor cost does not always encourage FDI. Based on this result, it can be concluded that perhaps investor tend to choose Indonesia as a host country based on its business and trade environment rather than the financial indicators. Keywords: FDI Determinants, Inflation, Export, Exchange Rate, Labor Cost, Granger Causality